Tle1 attenuates hepatic ischemia/reperfusion injury by suppressing NOD2/NF-κB signaling. Issue 6 (2nd June 2020) - Chen, Wei; Zheng, Daofeng; Mou, Tong; Pu, Junliang; Dai, Jiangwen; Huang, Zuotian; Luo, Yunhai; Zhang, Yuke; Wu, Zhongjun
ABSTRACT: Liver damage induced by ischemia/reperfusion (I/R) remains a primary issue in multiple hepatic surgeries. Innate immune-mediated inflammatory responses during the reperfusion stage aggravate the injury. Nevertheless, the detailed mechanism of hepatic I/R has not been fully clarified yet. Our research focuses on the role of Transducin-like enhancer of split-1 (Tle1) in the liver I/R injury and the relation between Tle1 and Nucleotide-binding oligomerization domain 2 (NOD2). To answer these questions, we constructed mouse models of I/R and cell models of hypoxia/reoxygenation (H/R). We found decreased Tle1 accompanied by increased NOD2 during reperfusion. Mice pro-injected with Tle1-siRNA emerged aggravated liver dysfunction. Repression of Tle1 had a significant impact on NOD2 and downstream NF-κB signaling in vitro . However, alteration of NOD2 failed to affect the expression of Tle1. To conclude, our study demonstrates that Tle1 shelters the liver from I/R injury through suppression of NOD2-dependent NF-κB activation and subsequent inflammatory responses. Graphical abstract: : During the hepatic ischemia/reperfusion injury, Tle1 reduces inflammation by regulating the NOD2/NF-κB signaling pathway.